2020
DOI: 10.21037/atm-19-4534
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative evaluation of sciatic nerve stiffness after compression by shear wave elastography in diabetic rats

Abstract: Background: Our study investigates the feasibility of using quantitative evaluation for nerve entrapment visualization by shear wave elastography (SWE) in diabetic rats.Methods: A total of 24 male Sprague-Dawley (SD) rats were included in this study. Before injection of streptozotocin (STZ), the experimental groups were assigned as the diabetic nerve compression (DNC) group (DNC, n=18) and the control group (CON, n=6). The DNC model was created by wrapping a silicone tube around the nerve, and then the DNC gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Additionally, previous studies that used SWE to evaluate nerve entrapment or DPN reported that the technique could detect an increase in nerve stiffness. In addition, nerve stiffness measured using SWE could better diagnose DPN than cross-sectional area (CSA) [ 9 10 ]. However, the clinical value of SWE in the early detection of DPN remains debatable.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, previous studies that used SWE to evaluate nerve entrapment or DPN reported that the technique could detect an increase in nerve stiffness. In addition, nerve stiffness measured using SWE could better diagnose DPN than cross-sectional area (CSA) [ 9 10 ]. However, the clinical value of SWE in the early detection of DPN remains debatable.…”
Section: Introductionmentioning
confidence: 99%
“…All of these will seriously endanger patients’ physical and psychological health and life safety. [ 16 , 17 ] There is no specific treatment clinically since the etiology and pathogenesis are unclear. At present, based on normal blood glucose, drugs can reverse neuropathy are often used for treatment, such as alprostadil, mecobalamin, and so on.…”
Section: Discussionmentioning
confidence: 99%